Evaluation of Drug Pre¬scription Pattern among Iraqi Dentists in Babylon City - Mohammed Abdul-Hassan Jabarah Al-Zobaidy (Journal of Global Pharma Technology, 2019)
Background: Drugs that are commonly prescribed by dentists include analagesics and antibiotics. However, the frequency of antibiotics prescription by dentists, whether for treatment or prvention of bacterial infections, is relatively lower than that by physicians. Also, the pregressive development of bacterial resistance to antibiotics called for seeking best-evidence on antibiotics ptrescription by practicing dentists to prevent the emergence of life-threatening antibiotic-resistant bacterial strains. Methods: Descriptive cross-sectional questionnaire-based study conducted in Babylon City, Iraq from August 2017 to January 2018. Data expressed as absolute numbers and proportions and presented using descriptive statistics. Results: In Babylon City, practicing dentists preferred amoxicillin as the first choice antibiotic for patients not allergic to penicillin; otherwise, macrolides and cephalosporins are recommended alternatives. In addition, mefenamic acid and ibuprofen were the preffered analgesics for pain relief. Also, participants often utilize clinical and scientific justifications for prescription of drugs in question. Conclusions: Dentists need to apply best-evidence concerning treatment of dental infections. And to actively participate in continuing professional development activities regarding antibiotics prescription. Keywords: Dentists, Antibiotics, Analgesics, Prescription for dental conditions, Pharmacology.